2021
DOI: 10.1111/jne.12940
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin‐dependent changes in neurosteroids are associated with increased aggression in a seasonally breeding rodent

Abstract: Aggression is a complex social behaviour that allows individuals to compete for access to limited resources (eg, mates, food and territories). Excessive or inappropriate aggression, however, has become problematic in modern societies, and current treatments are largely ineffective. Although previous work in mammals suggests that aggressive behaviour varies seasonally, seasonality is largely overlooked when developing clinical treatments for inappropriate aggression. Here, we investigated how the hormone melato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 108 publications
2
18
0
Order By: Relevance
“…We investigated individual consistency in social and escape behaviors across ontogeny using Siberian hamsters (Phodopus sungorus), which is an ideal, non-model system in which to test individual consistency in behavioral traits across time. Social and escape behaviors have been well documented in our lab population in both juveniles (Cusick et al, in review) and adults (Cusick et al in prep;Munley et al, 2021;Scotti et al, 2008;Sylvia et al, 2017), and are comparable to behaviors in wild populations (Ross, 1998). Social (e.g., aggressiveness, investigation) and escape behaviors are commonly measured traits in animal personality (e.g., Cabrera et al, 2021).…”
supporting
confidence: 68%
“…We investigated individual consistency in social and escape behaviors across ontogeny using Siberian hamsters (Phodopus sungorus), which is an ideal, non-model system in which to test individual consistency in behavioral traits across time. Social and escape behaviors have been well documented in our lab population in both juveniles (Cusick et al, in review) and adults (Cusick et al in prep;Munley et al, 2021;Scotti et al, 2008;Sylvia et al, 2017), and are comparable to behaviors in wild populations (Ross, 1998). Social (e.g., aggressiveness, investigation) and escape behaviors are commonly measured traits in animal personality (e.g., Cabrera et al, 2021).…”
supporting
confidence: 68%
“…Two-way multivariate analyses of variance (MANOVAs) were used to assess the effects of melatonin and photoperiodic treatment, sex, and the interaction between treatment and sex on PROG synthesis, AE synthesis, and the ratio of AE:PROG synthesis across tissues and brain regions. If a multivariate test reported a significant effect or a trend towards a significant effect ( p < 0.10) of treatment, sex, and/or the interaction between treatment and sex for one or more of the variables included in an analysis, two-way ANOVAs or generalized linear models (GLMs) and post-hoc testing (Tukey's HSD tests for two-way ANOVAs and Dunn's tests for GLMs) were conducted to examine pairwise comparisons (electronic supplementary material) [15,27].…”
Section: Methodsmentioning
confidence: 99%
“…We have shown that LD male and female hamsters given timed melatonin injections, which mimic an SD-like melatonin signal in circulation, show higher levels of aggression than LD hamsters given control injections and exhibit SD-like variation in baseline and aggression-induced circulating androgen and oestrogen levels [13,14]. We have also demonstrated that timed melatonin administration and exposure to SDs decreases concentrations of DHEA, T and E 2 in brain regions associated with aggression in male hamsters, including the anterior hypothalamus (AH) and periaqueductal gray (PAG) [15]. Recently, we determined that lentiviral-mediated overexpression of the MT 1 melatonin receptor, the primary melatonin receptor in Siberian hamsters, in the adrenal glands causes SD-like increases in aggression in male hamsters, but does not alter circulating DHEA levels [16], which could suggest that adrenal MT 1 receptors regulate seasonal aggression directly via neural substrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the winter months when resources are more limited and temperatures are low, animals tend to dedicate more energy to survival rather than reproduction (Walton et al, 2011). Aggression is a social behavior often crucial for survival as animals compete for limited resources and defend their territory (Munley et al, 2021). Because of the relationship between steroid hormones and aggression, the alteration or maintenance of aggression from the reproductive to nonreproductive seasons is of particular interest (Duque-Wilckens et al, 2019).…”
Section: Seasonal Aggressionmentioning
confidence: 99%